The effect of flotation reagents on the coagulation and dewatering of flotation tailings - Chidzala, Unaswi (Department of Chemical Engineering, 2025)
Sustainable water management in mining operations is necessary due to South Africa's water scarcity, especially in PGM mining, where flotation tailings pose serious difficulties. Water constitutes 80-85% of the mineral pulp in the flotation process, emphasising the significance of its role. However, water recycling from tailings dams and dewatering systems is becoming increasingly essential, yet it is impeded by the adverse effects of residual reagents on flotation selectivity. Utilising Merensky ore from the Bushveld Igneous Complex (BIC), this study examines how flotation reagents, including coagulants, flocculants, depressants, and collectors, affect the coagulation and dewatering of flotation tailings. The BIC has 75% of the world's platinum reserves and 50% of palladium reserves, making it one of the most commercially significant mineral deposits. The effects of different reagents, their combinations, and their effects on sedimentation, turbidity reduction, and particle size distribution (PSD) were assessed in a set of 15 tests. The study investigates coagulants (e.g., Fe2⁺ salts), that operate by charge neutralisation, and flocculants (e.g., polyacrylamides), that work through polymer bridging or patch processes. Systems which comprise flocculants or coagulants demonstrated higher settling rates, achieving turbidity reductions beyond 500 NTU/min within the initial five minutes, significantly exceeding the performance of systems utilising of only collectors or depressants. The combination of flocculants and coagulants in two-component systems resulted in the most fast settling rates, emphasising their synergistic effect. PSD analysis indicated that collector or depressant only systems retained particles under 200 μm, whereas flocculant and coagulant systems had broader distributions (up to 1100 μm), which corresponded with effective sedimentation. To improve polymer adsorption performance, tailored reagent optimisation exploited optimal particle size distributions and doses to overcome the obstacles presented by ultrafine particles (<1 μm). Rheological analyses demonstrated shear-thinning behaviour in coagulant-flocculant systems, decreasing slurry viscosity under shear to improve flowability, pumping efficiency, and dewatering. According to microstructural investigations (PSD, SEM), larger flocs improved sedimentation and reduced water entrainment, which is consistent with Stokes' law. These results demonstrate that flotation reagents can be strategically applied to improve dewatering efficiency and effectively tackle water recirculation challenges. The study stresses the optimisation of reagent combinations to enhance water quality for reuse in flotation and to promote dry stacking methods, hence facilitating sustainable mining in regions with limited water supplies.